Frequency of Stencil of Medico-legal Cases in Tertiary Hospital of Karachi (Medical Forum Monthly, 2020)
Objective: To determine the frequency and causes of medico-legal cases reported at three major hospitals of Karachi City.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the three major tertiary care hospitals of Karachi, Abbasi Shaheed Hospital, Jinnah Postgraduate Medical Centre and Civil Hospital, from January 2007 to December 2018.Materials and Methods: Total of 306,406 medico-legal cases in twelve years retrospective study period received at three major hospitals of Karachi were overseen. The data was collected with the permission of concerned authorities. Assault, Intoxication, Accident and Sexual Assault medico-legal cases were included in the study. A detailed examination was conducted in each case to determine the different causes of injury. Medico-legal deaths were excluded in the present study. The results were collected from the respective hospitals on a prepared structured Performa and were statistically analyzed using SPSS version 15.Results: Out of all, in our study, among medico-legal cases reported (306,406), assault cases were the predominant 190,029 (62.01%), followed by Intoxication 60,233 (19.65%), accident 47,543 (15.51%) and sexual assault cases, 8,601 (2.8%) respectively. Among the outnumber assault medico-legal cases, the commonest one caused by hard and blunt object 135,086 and amongst accident cases were of road traffic accident 30,896. In sexual assault cases, rape cases were about 5,505 and in Intoxication cases, 54,270 Poisoning were at highest.Conclusion: Hard and blunt injuries remained most common type of injury. Rape and poisoning cases are also recognized as most differentiating part of study. Enactment of the laws is the need of present period which can curtail accident cases and other medico-legal cases.